SWOG 1609 cohort 48: anti–CTLA‐4 and anti–PD‐1 for advanced gallbladder cancer - Patel, Sandip P.; Guadarrama, Elizabeth; Chae, Young Kwang; Dennis, Michael J.; Powers, Benjamin C.; Liao, Chih‐Yi; Ferri, William A.; George, Thomas J.; Sharon, Elad; Ryan, Christopher W.; Othus, Megan; Lopez, Gabby; et al. (Cancer, 2024)
Introduction Most patients with advanced gallbladder cancer are treated with multiagent chemotherapy. Immune checkpoint inhibitors offer the possibility of a durable response with less toxicity. This prospective, multicenter, open‐label study was designed to evaluate the anticancer activity of nivolumab plus ipilimumab in patients with advanced gallbladder cancer. Methods Nineteen patients with advanced gallbladder cancer refractory to ≥1 previous therapy received nivolumab 240 mg intravenously every 2 weeks and ipilimumab 1 mg/kg intravenously every 6 weeks until disease progression or unacceptable toxicity. The primary end point was confirmed radiographic overall response rate (ORR) (complete response [CR] + partial response [PR] confirmed on subsequent scan); secondary end points included unconfirmed overall response, clinical benefit rate (confirmed and unconfirmed responses + stable disease >6 months), progression‐free survival, overall survival, and toxicity. Results The confirmed ORR was 16% (CR, n = 1 [5%]; PR, n = 2 [11%]); all were microsatellite stable, and the confirmed CR had undetectable programmed death‐ligand 1 by immunohistochemistry. The unconfirmed ORR and clinical benefit rates were both 32%. The median duration of response was 14.8 months (range, 4–35.1+ months). The 6‐month progression‐free survival was 26% (95% CI, 12–55). The median overall survival was 7.0 months (95% CI, 3.9–19.1). The most common toxicities were fatigue (32%), anemia (26%), and anorexia (26%). Aspartate aminotransferase elevation was the most common grade 3/4 toxicity (11%). There was 1 possibly related death (sepsis with attendant hepatic failure). Conclusions Ipilimumab plus nivolumab was well tolerated and showed modest efficacy with durable responses in previously treated patients with advanced gallbladder cancer. Clinical Trial Registration NCT02834013 (ClincialTrials.gov). Plain Language Summary This prospective study assessed the efficacy and safety of nivolumab plus ipilimumab in 19 patients with advanced gallbladder cancer refractory to previous therapy. The combination demonstrated modest efficacy with a 16% confirmed overall response rate, durable responses, and manageable toxicities, suggesting potential benefits for this challenging patient population. Ipilimumab plus nivolumab demonstrated modest efficacy with durable responses and manageable toxicity in previously treated patients with advanced gallbladder cancer.